Sobre a lenha, labaredas : poética da memória e do esquecimento nas artes verbais krahô (Timbira/Brasil Central) - Packer, Ian, 1985- (2020)
Orientadores: Antonio Roberto Guerreiro Junior, Bruna Franchetto